Analysis of The Utilization of Solar Panels as Pump Crusters Automatically in Fish Pond Farming - Suwarti, Suwarti; H, Yusuf Dewantoro; Su'udy, Ahmad Hamim; Prasetyo, Budhi; Margana, Margana; W, Wiwik Purwati; Supriyo, Supriyo (Eksergi, 2023)
Abstract”” The purpose of making this final task is to apply the solar power system as a source of electrical energy to move the water pump automatically in fish ponds. This system works automatically with the Water Level Control tool sensor (WLC), so that if the water level drops or rises then the water pump will automatically work. On this automated system use the Smart Relay SR2B121BD and the ZelioSoft 2 application.  Data retrieval carried out at 10.00 -14.00 WIB, obtained data pumps 1 and 2 for a height of 1 cm for 30 minutes and a height of 2 cm for 70 minutes. The amount of discharge the pump produces 1 and 2 ranges from 37 L/M to 45 L/M.    Pump 1 Test results obtained an average efficiency of 7.68%, with the highest efficiency of 11.03% and the lowest efficiency of 5.26%, while the average pump efficiency of 2, 7.05% with the highest efficiency of 10.66% and the lowest efficiency of 5.41%. The average efficiency of the solar panels is 11.20% with the highest efficiency of 14.60% and the lowest efficiency of 7.29%.